Learning and change in the redesign of a primary health care initiative. Issue 7 (12th September 2016) - Rule, John; Dunston, Roger; Solomon, Nicky
Abstract : Purpose: This paper aims to provide an account of learning and change in the redesign of a primary health-care initiative in a large metropolitan city in Australia. Design/methodology/approach: The paper is based on research exploring the place and role of learning in the re-making of health professional practices in a major New South Wales Government health reform called HealthOne. The analysis and findings presented here make reference to data drawn from a longitudinal ethnographic study (2011-2014) conducted by an inter-disciplinary team of researchers from the University of Technology Sydney. Socio-material and practice-based approaches for understanding learning are used in working with the data. Findings: There were substantial changes in professional practice, especially in the role of the General Practice Liaison Nurse. Changes, and the learning connected to the changes, were dynamically influenced by the macro-context. HealthOne was a reform initiative with a strong focus on achieving health service redesign and a consistent focus on staff developing new ways of thinking and operating. Although learning was often discussed, it was, for the most part, expressed in general terms, and there was a lack of a formal and well-developed approach to learning collectively and individually. Originality/value: This research paper will inform future attempts at service redesign in community and primary health contexts and provides a site-specific examination of workplace learning in a context of rapid change.